Maxillectomy defects - to reconstruct or not? Pilot survey of Nigerian oral and maxillofacial surgeons - Abdurrazaq Olanrewaju Taiwo; Adebayo Aremu Ibikunle; Ramat Oyebunmi Braimah (Sahel Medical Journal, 2017)
Background: The choice of reconstruction options for maxillectomy defects varies significantly. Factors affecting it range from the type of defect to the surgeon's expertise. This study aims to evaluate the practice of Nigerian Oral and Maxillofacial surgeons in the reconstruction of post-maxillectomy defects. Materials and Methods: The survey was conducted by use of questionnaires administered at the annual scientific meeting of the oral and maxillofacial surgeons of Nigeria in Ibadan 2012. Results: A response rate of 66.7% was achieved. All of our respondents are consultant oral and maxillofacial surgeons, 80% of whom practice in a teaching hospital. All but one of them perform maxillectomies, however only 25% of them offer surgical reconstruction of the resulting defects to patients. Flaps have been used by 25% of the respondents, while none of them has employed microvascular reconstruction. Prosthetic rehabilitation of patients is pervasive among the respondents. Conclusion: Maxillectomy defects have far-reaching consequences on patients' quality of life and attempts should be made to reconstruct such defects. Although maxillectomy is a commonly performed procedure among oral and maxillofacial surgeons in Nigeria, especially for malignancies of the oral and paranasal sinuses, surgical reconstruction of resulting defects is not so frequently done. Microvascular surgery, which is becoming a frequently utilized option among surgeons in developed nations, is still infrequently used in our environment. There is a need for oral and maxillofacial surgeons in our climes to improve their skills so as to increase the range of reconstructive options offered.